Stunted Growth : Why Don't African Firms Create More Jobs? - Iacovone, Leonardo; Ramachandran, Vijaya; Schmidt, Martin (World Bank, Washington, DC, 2014)
Many countries in Africa suffer high rates of underemployment or low rates of productive employment; many also anticipate large numbers of people to enter the workforce in the near future. This paper asks the question: Are African firms creating fewer jobs than those located elsewhere? And, if so, why? One reason may be that weak business environments slow the growth of firms and distort the allocation of resources away from better-performing firms, hence reducing their potential for job creation. The paper uses data from 41,000 firms across 119 countries to examine the drivers of firm growth, with a special focus on African firms. African firms, at any age, tend to be 20-24 percent smaller than firms in other regions of the world. The poor business environment, driven by limited access to finance, and the lack of availability of electricity, land, and unskilled labor have some value in explaining this difference. Foreign ownership, the export status of the firm, and the size of the market are also significant determinants of firm size. However, even after controlling for the business environment and for characteristics of firms and markets, about 60 percent of the size gap between African and non-African firms remains unexplained.